An Analytical Study Of MSME Contributions To Social Development In Bareilly Division Through The Lens Of Social Entrepreneurship - Ms. Brij Lally; Prof. (Dr.) Anurag Agarwal (Revista Electronica de Veterinaria)
This research paper explores the correlation between Micro, Small and Medium Enterprises (MSMEs) and the accessibility of basic services in four districts of Bareilly Division, Uttar Pradesh: Bareilly, Shahjahanpur, Budaun and Pilibhit. Grounded in the context of social entrepreneurship, the study investigates the hypothesis that districts with higher MSME density are more likely to possess adequate infrastructure for electricity, sanitation, safe drinking water and healthcare. Utilizing quantitative data on registered MSMEs and service coverage percentages, the study employs a ranking methodology to analyze the socio-economic landscape of these districts. The paper integrates ancient Indian wisdom through Sanskrit shlokas to contextualize the concept of duty and community welfare (Dharma) within modern entrepreneurship. The findings reveal a strong positive correlation between MSME density and service accessibility, suggesting that industrial growth acts as a catalyst for social development. The conclusion offers policy recommendations to foster social entrepreneurship in semi-urban Uttar Pradesh.